2020
DOI: 10.3390/antibiotics9100677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvants on Oxytetracycline Uptake upon Foliar Application in Citrus

Abstract: Recently in Florida, foliar treatments using products with the antibiotics oxytetracycline and streptomycin have been approved for the treatment of citrus Huanglongbing (HLB), which is caused by the putative bacterial pathogen ‘Candidatus Liberibacter asiaticus’. Herein, we assessed the levels of oxytetracycline and ‘Ca. L. asiaticus’ titers in citrus trees upon foliar applications with and without a variety of commercial penetrant adjuvants and upon trunk injection. The level of oxytetracycline in citrus leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…The injection solution was prepared by dissolving 100.0 g (equivalent to 17.3 g of pure OTC) of Fireline 17 WP (Agro Source, Tequesta, FL, USA) in 200 mL of water. Each tree was injected with a 20-mL aliquot of the Fireline solution (equivalent to 1.7 g OTC) using a 20-mL Chemjet manual injector (Healthy Tree PHC, Inc., Norfolk, VA, USA) as described previously [ 7 ]. The injector was left overnight until all the solution was taken by the tree.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The injection solution was prepared by dissolving 100.0 g (equivalent to 17.3 g of pure OTC) of Fireline 17 WP (Agro Source, Tequesta, FL, USA) in 200 mL of water. Each tree was injected with a 20-mL aliquot of the Fireline solution (equivalent to 1.7 g OTC) using a 20-mL Chemjet manual injector (Healthy Tree PHC, Inc., Norfolk, VA, USA) as described previously [ 7 ]. The injector was left overnight until all the solution was taken by the tree.…”
Section: Methodsmentioning
confidence: 99%
“…A trace amount of OTC (202 µg/kg) was detected in fruits nine months after treatment [ 6 ]. Recently, we showed that trunk injection of OTC was more efficient than foliar application [ 7 ]. The C Las titer was significantly reduced in oxytetracycline-injected trees thirty days after treatment, whereas it was not affected by foliar application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of OTC in the phloem beyond the girdling indicated that OTC could be translocated from the xylem to the phloem during acropetal movement [ 8 ]. Recently, we studied the uptake of OTC by citrus trees in the field after trunk and foliar application [ 9 ]. Our results showed that foliar spray of OTC was less effective than trunk injection [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we studied the uptake of OTC by citrus trees in the field after trunk and foliar application [ 9 ]. Our results showed that foliar spray of OTC was less effective than trunk injection [ 9 ]. Higher levels of OTC (~5 µg g −1 FWT) were found in trunk-injected trees compared with those treated using the foliar application (~0.1 µg g −1 FWT) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%